Integrated systems of agricultural production and agroecological alternative (Cuban experience) (Revista Sistemas de Producción Agroecológicos, 2011)
Specialized production systems generally require exogenous flow of resources and their maintenance and stability does not depend on its ability to sustain itself. In contrast, agroecological production systems, facing processes, show greater carrying capacity, generating synergies that may enhance natural abilities to produce food of plant and animal origin and to restore balance productive, ecologically and economically, to the influence refusal of any internal or external factor. A system is considered the sum of its parts, but the result of all, made by the parties. In agroecological systems implanted rationality not only biological functioning of soil, plants and animals, but is related to man and their social, economic and political. Here is discarded anthropocentric view of the world and takes place biocentric vision, which explains the functioning and evolution of any changes. Another aspect to consider are the traditional techniques and local knowledge. The experience acquired traditional and local knowledge, including empirical, agricultural activity is transmitted from generation to generation and are very important to achieve productive and efficient results.
Keywords: agricultural systems; ecology; Cuba